Pengendalian Gratifikasi Berbasis Web - Alexander Dharmawan (Electro Luceat, 2022)
The seriousness of the Central Java Provincial Government in controlling gratification began with the issuance of Gubernatorial Regulation No. Gratification must be reported to the Gratification Control Unit (UPG) if it is directly related to the position and contrary to the task. The existing control system can be said to be not optimal, the report data is still not stored and integrated in the same storage media. Gratification reports are collected via email or fill out a form in person at the Inspectorate building. Public complaints are collected through the Inspectorate's website. This causes the report recapitulation process to be less efficient and effective. For this reason, it is necessary to have an e-government system for integrated web-based gratification control. The system is built using the Bootstrap framework and is supported by PHP functions with MySQL-based storage. As a result, data on gratification reports and public complaints related to gratification cases within the Central Java Provincial Government can be recapitulated by the Central Java UPG more effectively and efficiently.